Separability and geometry of object manifolds in deep neural networks - Uri Cohen (Nature Portfolio, 2020)
Neural activity space or manifold that represents object information changes across the layers of a deep neural network. Here the authors present a theoretical account of the relationship between the geometry of the manifolds and the classification capacity of the neural networks.